Peace Indicating Words in Pre- Islamic Poetry (Journal of the College of Education for Women, 2019)
In pre- Islamic poetry, there are a lot of words that indicatepeacefulness of one sort of another, in addition to the inspirations of semanticmodeling in which the poet sets himself in various horizons.Among these words: brother, comrade, friend, companion, lover,people, prince, home, land, country, blessing, honesty, contract, company,justice, thankfulness, forgiveness, pardoning, guest, goodness, faithfulness,silence, death, peace,….In addition, there are their derivatives from various aspects that indicatepeacefulness either directly or indirectly.